(3EfHGA GdZeQ HCHfGA GdYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3eG HYO jbhd GdYHO GdVYja CMeO Hf Ydi Hf eMeO Hf eMeO Hf Ydi GdYSbdGfi GdCUd GdeUQi GdehdO s
(3BNQgG (B:s
(3hdcfg de jcf aef jJhLg Edi gPG GdfhY HcdjJg hjbdO ai cHQ Sfg HYV ef jZdH Ydi Xfg JKHJg hbO dGjchf PGc TGgOg Hd jdbGg Yf ZjQ VGHW hGdCeQ ai Pdc Sgd dg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B34 s
Keywords: (3GdJGQjNs